2017
DOI: 10.1016/j.ijpddr.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of constitutive and thiabendazole-induced expression of five cytochrome P450 genes in fourth-stage larvae of Haemonchus contortus isolates with different drug susceptibility identifies one gene with high constitutive expression in a multi-resistant isolate

Abstract: Benzimidazoles (BZs) remain amongst the most widely used anthelmintic drug classes against gastro-intestinal nematode infections, although their efficacy is increasingly compromised by resistance. The primary underlying mechanisms for BZ resistance are single-nucleotide polymorphisms (SNPs) in the isotype 1 β-tubulin gene causing the substitutions F167Y, E198A or F200Y. However, resistance is believed to be multi-genic and previous studies have shown that isolates carrying 90–100% F200Y can vary considerably i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…However, this view has been changed with the discovery of CYPs-encoding genes in C. elegans, where more than 80 CYP proteins are present [85,86], and these have been shown to be xenobiotics inducible [85,[87][88][89][90]. The CYPs family have also been characterized recently in H. contortus [91,92]. ABC transporter and pgp fall under the phase III of xenobiotic detoxification process.…”
Section: Discussionmentioning
confidence: 99%
“…However, this view has been changed with the discovery of CYPs-encoding genes in C. elegans, where more than 80 CYP proteins are present [85,86], and these have been shown to be xenobiotics inducible [85,[87][88][89][90]. The CYPs family have also been characterized recently in H. contortus [91,92]. ABC transporter and pgp fall under the phase III of xenobiotic detoxification process.…”
Section: Discussionmentioning
confidence: 99%
“…Benzimidazole suppressor screens in both Saccharomyces cerevisiae and Caenorhabditis elegans have independently identified resistance mutations occuring in β-tubulin genes, giving some insight into the binding site 29,30 . The case for a β-tubulin binding site is strengthened by numerous animal and agricultural studies also demonstrating resistance mutations arising repeatedly and independently across multiple parasitic nematode and fungal species infecting farm livestock and crops 22,27,[31][32][33][34][35][36][37][38][39][40][41][42][43] .…”
Section: Thiabendazole Disrupts Microtubule Plus Ends In Endothelial mentioning
confidence: 99%
“…Three commonly observed mutations in fungal and nematode β-tubulins (F200Y, E198A, and F167Y) confer resistance to TBZ ( Fig. 2A, B), suggesting that its binding site is in the vicinity of these residues 22,27,[31][32][33][34][35][36][37][38][39][40][41][42][43] (File S1). Based on the previously observed benzimidazole suppressor 6 mutations, we used 3D structural modeling to evaluate TBZ's potential binding sites in a fungal β-tubulin.…”
Section: Thiabendazole Selectively Targets Tubb8 Among Human β-Tubulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase I enzymes of the cytochrome P450-family (CYP) have been shown to be involved in drug resistance in insects (27), but the involvement of phase I and II enzymes in anthelmintic resistance of parasitic nematodes has not been thoroughly investigated, particularly not in ascarids. However, constitutively higher expression of a CYP34/35 family member (28) as well as the phase II enzyme uridine 5'-diphospho-glucuronosyltransferase-glucosyltransferase (UGT) (29) have been found in BZ resistant strains of H. contortus. Several studies have also shown evidence for upregulation of genes encoding drug efflux pumps, such as ATP-binding cassette (ABC) transporters, in macrocyclic lactone resistant strongyle nematodes (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%